2004
DOI: 10.1109/tns.2004.824827
|View full text |Cite
|
Sign up to set email alerts
|

Custom Breast Phantom for an Accurate Tumor SNR Analysis

Abstract: The capability of the scintimammography to diagnose subcentimeters sized tumors was increased by the employment of a dedicated gamma camera. The introduction of small field of view camera, based on pixellated scintillation array and position sensitive photomultiplier, allowed to enhance the geometric spatial resolution and contrast of the images due to reduced collimator-tumor distance.The aim of this paper is to investigate the realistic possibility of T1a tumors detection ( 5 mm size) by comparing the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although a simple geometry has been used to simulate breast, tumors and heart, there are several studies that have used this approach for evaluating and optimizing scintimammography systems and techniques, using either clinical cameras [24,[32][33][34] or dedicated prototypes [34,35]. Real clinical studies are obviously more complicated, but even such simple phantoms can provide adequate information regarding the limitations of existing systems and indicate possible improvements in hardware and data acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a simple geometry has been used to simulate breast, tumors and heart, there are several studies that have used this approach for evaluating and optimizing scintimammography systems and techniques, using either clinical cameras [24,[32][33][34] or dedicated prototypes [34,35]. Real clinical studies are obviously more complicated, but even such simple phantoms can provide adequate information regarding the limitations of existing systems and indicate possible improvements in hardware and data acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The specific radioactivity of the breast phantom was 2 µCi/ml. These values were selected by reviewing the literature and determining the lowest T:B ratios or tumor volumes [17,19,24]. The acquisition time was 300secs in all measurements, which approximates a typical scintimammography examination, although studies lasting as long as 10 min have been reported [9].…”
Section: Methodsmentioning
confidence: 99%
“…Custom software was developed to process and elaborate data for spectra analysis. More details about this readout can be found in other references [8,9].…”
Section: 21mentioning
confidence: 99%